Implementasi Metode Backward Chaining pada Sistem Pakar Analisis Risiko Penularan Demam Berdarah Dengue (DBD) dan Penilaian Kesiapan Program Wolbachia Ing Kota (WINGKO) Semarang - Vic Jeremy Prajogo; Siska Narulita; Aerrosa Murenda Mayadilanuari (Universitas Stikubank, 2026)
The high number of Demam Berdarah Dengue (DBD) cases poses a challenge to public health. The successful implementation of Wolbachia technology innovation depends on the analysis of transmission risks and community readiness. This research aims to develop an integrated expert system capable of performing both assessments using research and development methods. This expert system is designed to implement the backward chaining inference method as its primary reasoning mechanism in constructing a structured diagnostic flow. System testing was conducted using the blackbox testing method based on equivalence partitioning to test the system's functionality. The testing results involving users yielded a success rate of 99.28%. This indicates that all the test cases designed were successfully executed, but there was still a 0.72% discrepancy in features or functions.